Proteomics profiling of inflammation-related biomarkers in antidepressant treatment response: Findings from the CO-MED trial - Gadad, Bharathi S. (J Psychiatr Res, 2017)
Animal and human studies suggest an association between depression and aberrant immune response. Further, common inflammatory markers may change during the course of antidepressant treatment in patients. The objective of this study was to evaluate changes in inflammatory markers and clinical outcomes from subjects enrolled in the Combination of Medications to Enhance Depression Outcome (CO-MED) trial. At baseline and week 12 (treatment completion), plasma samples of 102 participants were analyzed via a multiplex assay comprised of inflammatory markers using a 27-plex standard assay panel plus a 4-plex human acute phase xMAP technology based platform. We carried out analyses in two steps. First, t-tests were used to identify inflammatory marker levels that changed between baseline and week 12. For markers that were altered, logistic regression models were then conducted to look for associated changes in remission at week 12. Among the 31 inflammatory markers analyzed, several cytokines (IL-5, IFN-γ, IL-13), two chemokines (Eotaxin-1/CCL11, RANTES) and an acute-phase reactant (serum amyloid P component) showed change from baseline to week 12. However, only two indicated differential remission responses. Interestingly, increased levels of Eotaxin-1/CCL11 correlated with remission at week 12, whereas decreased levels of IFN-γ correlated with non-remission at week 12. Results suggest that these inflammatory proteins may serve as predictors of treatment response.